Providing medical care for undocumented migrants in Denmark: what are the challenges for health professionals? - Priebe Stefan; Bogic Marija; Draebel Tania; Norredam Marie; Jensen Natasja K; Krasnik Allan (BMC, 2011)
Abstract Background The rights of undocumented migrants are frequently overlooked. Denmark has ratified several international conventions recognizing the right to health care for all human beings, but has very scanty legislation and no existing policies for providing health care to undocumented migrants. This study focuses on how health professionals navigate and how they experience providing treatment for undocumented migrants in the Danish health care system. Methods The study was carried out as part of an EU-project on European Best Practices in Access, Quality and Appropriateness of Health Services for Immigrants in Europe (EUGATE). This presentation is based on 12 semi-structured interviews with general practitioners (9) and emergency room physicians (3) in Denmark. Results The emergency room physicians express that treatment of undocumented migrants is no different from the treatment of any other person. However, care may become more complicated due to lack of previous medical records and contact persons. Contrary to this, general practitioners explain that undocumented migrants will encounter formal barriers when trying to obtain treatment. Additional problems in the treatment of undocumented migrants include language issues, financial aspects for general practitioners, concerns about how to handle the situation including possibilities of further referrals, and an uncertainty as to whether to involve the police. Conclusions The health professionals in our study describe that undocumented migrants experience an unequal access to primary care facilities and that great uncertainties exist amongst health professionals as how to respond in such situations. The lack of official policies concerning the right to health care for undocumented migrants continue to pass on the responsibility to health professionals and, thereby, leaves it up to the individual to decide whether treatment can be obtained or not.